Spletne učilnice šolske knjižnice Osnovne šole Prule - Škrlj, Gregor (Šolska knjižnica, 2012)
The paper describes four e-classrooms used for library work in a primary school library. It also shows the design, making and use of the e-classrooms. Presented are School library for the pupils, Library club, Teaching library and information knowledge, and Library for the teachers which is a part of teachers' staff room. The school library joins the classical and modern teaching, known as crosscurricular connection with the use of new technologies. This enhances and develops basic literacies and competences (information, computer, digital).
Keywords: osnovne šole; pouk; spletne učilnice; šolske knjižnice; učenci